Analisis Faktor Hospitaliti Masyarakat Terhadap Wisatawan di Kawasan Kota Bogor - Resista Vikaliana (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
Bogor city has a natural phenomenon as a tourist destination. Therefore, until now when entering the holiday period, Bogor City is always crowded by tourists. To promote tourism in the city of Bogor, it is necessary necessary facilities that can support such as hospitality industry. The existence of hospitality industry in the city of Bogor becomes a very big attraction for tourists both for the purpose of seeking entertainment or for business purposes. Based on information obtained by tourists on the existence of tourist destinations in the city of Bogor, the tourists are interested to travel by spending time and money to satisfy curiosity.This research is conducted to learn more with the formulation of the problem as the factors of what hospitals can satisfy tourists who visit the city of Bogor?The research approach used in this research is quantitative approach. While this type of research is descriptive research. Descriptive research aims to describe or describe a research object.Technique of taking data using primary and secondary data. Primary data were taken using questionnaire. Questionnaires were distributed to 100 travelers with sampling technique of cluster sampling, at Bogor Botanical Garden object, Taman Hat / Taman Ade Irma Suryani and Suryakencana Culinary Tour. Data were analyzed using factor analysis.Based on the result of the research, it can be concluded that of the 24 most influential community hospital factors on tourist visit in Bogor City can be grouped into 7 components or variables.